Physical and chemical properties for oil palm cultivation based on smallholder landin four different type of soils - Ahmad, Mohd Firdaus (2015)
Oil palm is an important commodity (industrial crop) in Malaysia because it contributes high revenue to Malaysia economy. In 2012, small holder participation were about 15.1% (767,688 ha) from 5.07 million hectare total area planted with oil palm. The suitability of land for oil palm cultivation consists of topography, drainage, physical and chemical properties. These characteristics influence the palm oil yield. Thus, study on land suitability and fertility for oil palm plantations in smallholder is important. Difficulties of smallholder to get the information about the classification and guidance in oil palm plantation ofteninflunce smallholder capability to survive and grow in oil palm industry. Thus, the objectives of this study is: i) to determine the physical and chemical properties of oil palm land of smallholder and, ii) to identify productivity level between different soils (alluvium, mineral, BRIS and acid sulphate soil) in term of economics impact relation with oil palm and land suitability. In this study, soil samples were collected from four locations. Each of the smallholders have land size of (<2.5ha). The selected areas were at Hulu Langat (Selangor) and ParitBotak(Johor). For alluvium, mineral and acid sulphate soils, the sample were taken in Johor and for BRIS soil; the sample were taken in Selangor. Soil samples were collect at two different depths which are 0-15 cm for top soil and 15 – 45 cm for effective depth to uptake nutrient because oil palm have fibrous root. The samples were collected using a an auger in which 12 sample were taken randomly for each plot. Hence, a total of 48 soil samples were collected for determination of physical and chemical properties. Soil analyse includes pH, CEC, exchangeable bases, N, P, K, soil structure, soil texture, colour and soil moisture. Atomic Absorption Spectrometer (AAS) were used to quantify macro nutrient content (N, P, K, Ca and Mg).The fertility of the soils and land suitability known to affect oil palm. From this study,Alluvium soil contains highest clay (34%) , high in CEC (12.39 cmolc/kg), high in available P (5.25 ppm) and soil pH (5.12) that suitable for Oil palm cultivation. Meanwhile, BRIS and acid sulfate soil can be categorized as a problematic area for oil palm cultivation. Acid sulfate soil more acidic and contain a jarosite not suitable for crop. Besides, BRIS soil not fertile because less in water holding capacity and the soil is more sandy. Organic fertilizer such as manure, compose and mulching are recommend also in problematic soil. This can help to improve soil structure, soil CEC, increase water holding capacity and promote microorganism activity. It can also help in reducing water loss through evapotranspiration and cooling the soil surface to retain the moisture.